1995
DOI: 10.1016/0304-3959(94)00206-t
|View full text |Cite
|
Sign up to set email alerts
|

Musculoskeletal pains and depression in a middle-aged finnish population

Abstract: The relationships between depression, measured as high rates of depressive symptoms (Zung Self-Rating Depression Scale, ZSDS), and musculoskeletal pains (Kuorinka et al. 1987) were described in a 55-year-old Finnish population consisting of all the 1008 persons born in 1935 and living in the city of Oulu on 1 October 1990. Three hundred forty-five men (76%) and 435 women (79%) participated in the examinations. Of the men 6.8% and of the women 12.1% scored 45 raw sum points or more on the ZSDS. In several anato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0
5

Year Published

1999
1999
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(38 citation statements)
references
References 14 publications
1
32
0
5
Order By: Relevance
“…Previous studies have shown that chronic pain constitutes a major public health problem. Estimates vary, depending on the survey and on the anatomical site of interest, but community surveys conducted in Western Europe and North America have reported that as many as 25-50% of the adult population may suffer from some form of chronic pain (Bovim and Schrader, 1994;Rajala and Keinanen-Kiukaanniemi, 1995;Palmer and Walsh, 2000;Santos-Eggiman and Wietlisbach, 2000;Picavet and Schouten, 2003;Von Korff and Crane, 2005). The results of the World Mental Health Surveys also show that chronic pain problems are common world-wide, in both developed and developing countries.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that chronic pain constitutes a major public health problem. Estimates vary, depending on the survey and on the anatomical site of interest, but community surveys conducted in Western Europe and North America have reported that as many as 25-50% of the adult population may suffer from some form of chronic pain (Bovim and Schrader, 1994;Rajala and Keinanen-Kiukaanniemi, 1995;Palmer and Walsh, 2000;Santos-Eggiman and Wietlisbach, 2000;Picavet and Schouten, 2003;Von Korff and Crane, 2005). The results of the World Mental Health Surveys also show that chronic pain problems are common world-wide, in both developed and developing countries.…”
Section: Discussionmentioning
confidence: 99%
“…Segundo o referido autor, citando estudo de Rajala 13 , na Finlândia, a dor músculo-esquelética crônica foi diagnosticada em 32,1% dos homens deprimidos, em 26,7% dos não deprimidos, e em 36,7% das mulheres deprimidas e em 31,2% das não deprimidas.…”
Section: Discussionunclassified
“…Cervical disorders are common and are frequently disabling and costly [1][2][3][4]. Cervical disorders can be classified into specific and non-specific disorders, such as cervical radiculopathy, discopathy and spondylosis.…”
Section: Introductionmentioning
confidence: 99%